2020
DOI: 10.1186/s12889-020-8237-4
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: randomized controlled trial of manualized components in home visitation to reduce mothers’ risk for child maltreatment

Abstract: Background: This study tests whether home visitation to prevent child maltreatment can be improved by adding manualized program components, targeting four key risk factors for child maltreatment: low parental self-efficacy, high levels of perceived stress, parental anger, and post-traumatic stress symptoms. Home visitation is widely implemented, but effects on child maltreatment risk tend to be modest at best. Home visitation tends to be rather flexible (i.e., professionals decide how to support each family). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Other early work linked parental stress with anger in relation to parents’ abuse risk [ 41 , 42 ], suggesting that reductions in negative affect from both stress and anger could decrease risk for abuse. A treatment program focused on both attributional retraining and anger management to reduce parents’ abuse risk demonstrated that parents perceived fewer child problem behaviors after treatment [ 43 ], consistent with other programs that incorporate parent training in regulating anger [ 44 ]. Such treatment effects suggest that reductions in parental anger and negative attributions can precipitate changes in parents’ perceptions of child behavior problems.…”
Section: Introductionmentioning
confidence: 72%
“…Other early work linked parental stress with anger in relation to parents’ abuse risk [ 41 , 42 ], suggesting that reductions in negative affect from both stress and anger could decrease risk for abuse. A treatment program focused on both attributional retraining and anger management to reduce parents’ abuse risk demonstrated that parents perceived fewer child problem behaviors after treatment [ 43 ], consistent with other programs that incorporate parent training in regulating anger [ 44 ]. Such treatment effects suggest that reductions in parental anger and negative attributions can precipitate changes in parents’ perceptions of child behavior problems.…”
Section: Introductionmentioning
confidence: 72%
“…The current study extends that work, demonstrating that anger was related to all three forms of maltreatment risk during the pandemic. This expansion has relevance for prevention programming, some of which incorporate anger management (Altafim & Linhares, 2016;Sanders et al, 2004;de Wit et al, 2020); the present findings suggest anger should be more widely adopted in an effort to broadly reduce maltreatment risk. Limited data has been available on the experience of anger and frustration during the pandemic (APA, 2020), despite its potential relevance to child maltreatment risk.…”
Section: Discussionmentioning
confidence: 71%
“…However, parents' emotions are recognized contributors to child maltreatment risk (see Stith et al, 2009 for review), and theorists have urged more consideration of affective factors (Milner, 2000;Rodriguez & Pu, 2020). In particular, parents' anger has received the most empirical inquiry, with research demonstrating that anger relates to risk for physical abuse and neglect (McCarthy et al, 2016;Rodriguez & Richardson, 2007;Pidgeon & Sanders, 2009;Stith et al, 2009), exacerbates cognitive factors (Rodriguez, 2018), mediates the association between childhood abuse history and parental maltreatment risk (Smith et al, 2014), and represents a target in some abuse prevention programs (e.g., Altafim & Linhares, 2016;Sanders et al, 2004;de Wit et al, 2020). Notably, much of the work that has evaluated anger in child maltreatment risk has focused on physical abuse, with substantially less attention to the connection between parents' anger and neglect (Stith et al, 2009) or between anger and psychological aggression (Rodriguez & Richardson, 2007).…”
Section: Parental Affect and Maltreatment Riskmentioning
confidence: 99%
“…The current study extends that work, demonstrating that anger was related to all three forms of maltreatment risk during the pandemic. This expansion has relevance for prevention programming, only some of which incorporate anger management (Altafim & Linhares, 2016 ; Sanders et al, 2004 ; de Wit et al, 2020 ). The present findings suggest anger management should be more widely adopted in an effort to broadly reduce maltreatment risk, but also with particular attention to anger directly in response to perceived child misbehavior.…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ anger in particular has garnered the most empirical inquiry, with research demonstrating that anger relates to risk for physical abuse and neglect (McCarthy et al, 2016 ; Rodriguez & Richardson, 2007 ; Pidgeon & Sanders, 2009 ; Stith et al, 2009 ), exacerbates maternal cognitive risk factors in physical child abuse risk (Rodriguez, 2018 ), and mediates the association between childhood abuse history and maternal physical abuse risk (Smith et al, 2014 ). Thus, although most abuse prevention programs focus on shifting cognitions, some programs incorporate anger management components based on the premise that a greater tendency to experience anger will be invoked to result in maltreatment behavior (e.g., Altafim & Linhares, 2016 ; Sanders et al, 2004 ; de Wit et al, 2020 ). Notably, most of the work that has evaluated anger in relation to child maltreatment risk has focused on physical abuse, with less attention in the literature (either pre-pandemic or during the pandemic) to whether parental anger is linked to their psychological aggression or neglect.…”
Section: Parental Affect and Maltreatment Riskmentioning
confidence: 99%